Pengaruh Marketing Mix Terhadap Keputusan Pembelian Kopi Janji Jiwa Mall Kelapa Gading - Augustiene Riyanti Widjaya; Anjar Dwi Astono (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of product, price, place and promotion variables on purchasing decisions. There are five variables in this study, namely product, price, place, promotion and purchase decisions. Researchers used quantitative methods and the sample used in this study amounted to 140 respondents. who is a customer of Janji Jiwa. The technique used in this research is purposive sampling which is part of non-probability sampling. The research data analyzed using SPSS 23 shows that product variables have a significant effect on purchasing decisions, price variables do not significantly influence purchasing decisions, place variables have a significant effect on purchasing decisions. significant on purchasing decisions, Promotion variable has a significant effect on purchasing decisions.